Pengaruh Kepercayaan, Citra Perusahaan, dan Promosi Penjualan Terhadap Kepuasan Nasabah Lembaga Perkreditan Desa LPD Desa Pakraman Guwang Kabupaten Gianyar - KADEK WIDIANTARA; I NYOMAN GEDE USTRIYANA; A. A. A. WULANDIRA SAWITRI DJELANTIK (Agribusiness Study Program, Faculty of Agriculture, Udayana University, 2022)
The Influence of Trust, Torporate Image, and Sales Promotion on Customers’ Satisfaction on the Pakraman Guwang Village Credit Institution in Gianyar Regency. This study aims to identify the influence of trust, corporate image, and sales promation on customers’ satisfaction on the Pakraman Guwang Village Credit institution in Sukawati District, Gianyar Regency. Primary data were obtained through intervews and observation. Using Stuctural Equation Modeling (SEM), which includes validity, reliability, multicollinearity, simultaneous and hypothesis testing, this study show that trust, company image, and sales promation have a significant and simultaneuos effect on satisfactoion. In addition, there is a partial significant influence betwen trust, company image, and sales promation on satisfaction. Pakraman Guwang Village Credit institution needs to carry out more attractive promotions to increase customer satisfaction. In addition, increasing trust can be done by guaranteeing the confidentiality and safety of customers’ money/assets or during transaction. Future research may consider adding variables to better understand customer satisfaction.